Medium to long term follow up study of the efficacy of cessation of eye-rubbing to halt progression of keratoconus - Mazharian, Adrien; Flamant, Roxane; Elahi, Sina; Panthier, Christophe; Rampat, Radhika; Gatinel, Damien (Frontiers in Medicine, 2023)
Purpose To study the progression of keratoconus after cessation of eye rubbing with a minimum follow up of three-years. Design Retrospective, monocentric, longitudinal cohort study of keratoconus patients with a minimum of 3 years follow-up. Participants One hundred fifty three eyes of seventy-seven consecutive patients with keratoconus were included. Methods Initial examination consisted of anterior and posterior segment evaluation using slit-lamp biomicroscopy. At the initial visit, patients were thoroughly informed of their pathology and instructed to stop rubbing their eyes. Eye rubbing cessation was assessed at all the follow-up visits at 6 months, 1 year, 2 years, 3 years, and yearly afterward. Corneal topography using the Pentacam® (Oculus®, Wetzlar, Germany) was used to obtain maximum and average anterior keratometry readings (Kmax and Kmean), as well as thinnest pachymetry (Pachymin, μm) in both eyes. Main outcome measures The main outcomes measured were maximum keratometry (Kmax), mean keratometry (Kmean), and thinnest pachymetry (Pachymin) values at various time points to assess for keratoconus progression. Keratoconus progression was defined as a significant augmentation of Kmax (>1D), Kmean (>1D), or significant diminution of Pachymin (>5%) throughout the total follow-up duration. Results One hundred fifty three eyes of seventy-seven patients (75.3% males) aged 26.4 years old, were followed for an average of 53 months. Over the course of the follow-up, there was no statistically significant variation of ∆Kmax (+0.04 ± 0.87; p = 0.34), ∆ Kmean (+0.30 ± 0.67; p = 0.27) nor ∆Pachymin (−4.36 ± 11.88; p = 0.64). Among the 26 of the 153 eyes which had at least one criterion of KC progression, 25 admitted continuing eye rubbing, or other at-risk behaviors. Conclusion This study suggests that a significant proportion of keratoconus patients are likely to remain stable if close monitoring and strict ARB cessation are achieved, without the need for further intervention.